2021
DOI: 10.1016/j.jeurceramsoc.2020.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of additive manufacturing processes to build ceramic/metal parts: Example of HTCC

Abstract: Stereolithography is an additive manufacturing process, which makes it possible to fabricate useful complex 3D ceramic parts with a high dimensional resolution, a good surface roughness and properties close to those obtained by classical routes. Previous work concerning LTCC components, demonstrates that it is possible, by coupling the stereolithography with robocasting additive processes, to obtain multi-material components (e.g. ceramic / metal components). On the base of this previous work, the manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…One promising alternative to true multimaterial printing is the subsequent printing of different materials, and cosintering of these to make the finished part. This, as stated, does require thorough consideration of relevant conditions and shrinkage effects (Raynaud et al, 2020(Raynaud et al, , 2021.…”
Section: Multi-materials Printingmentioning
confidence: 99%
“…One promising alternative to true multimaterial printing is the subsequent printing of different materials, and cosintering of these to make the finished part. This, as stated, does require thorough consideration of relevant conditions and shrinkage effects (Raynaud et al, 2020(Raynaud et al, , 2021.…”
Section: Multi-materials Printingmentioning
confidence: 99%
“…Delage et al printed silver millimeter-wave transmission lines on the surface of sintered 3D Al 2 O 3 ceramic structures via the aerosol jet process . Raynaud et al integrated ceramic stereolithography (SLA) 3D printing and silver paste dispensing to deliver high-temperature cofired ceramic (HTCC)- and low-temperature cofired ceramic (LTCC)-based electronics. , In our previous work, a multimaterial dispensing additive manufacturing technology was presented, which fabricated 3D electronics via alternatively printing silver paste and an LTCC slurry layer-by-layer . However, these HAM technologies have common shortcomings of low fabrication precision and limited electrical performance as a result of large shrinkage after sintering and conductive ink/paste used, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…50 µm), which will likely require the adaptation of the ink formulation. Previous works, and those of J. Raynaud [1], [5], [10], have shown that the use of tungsten presents some limitations. Indeed, in addition to a moderate electrical conductivity (σ W = 8.9 .10 6 S.m -1 ), delamination at the ceramic/metal interfaces were observed due to a high difference of Coefficient of Thermal Expansion (CTE) between tungsten (CTE = 4,4.10 -6 K -1 ) and alumina (CTE = 7.1 10 -6 °C-1 ).…”
Section: I1 Introductionmentioning
confidence: 99%